Dampak Harga Dan Tempat Terhadap Pilihan Pelanggan Dalam Berbelanja Di KDS Department Store & Supermarket Bojonegoro - Reza Anggapratama; Dwi Irnawati (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2022)
This research is to see the impact of price and place on customer choice in shopping at KDS Department Store & Supermarket Bojonegoro. This research is using descriptive with consumer research object KDS Department Store & Supermarket Bojonegoro. At this time the Department Store & Supermarket is an alternative shopping place for consumers to meet their needs. KDS is a Department Store and Supermarket in Bojonegoro. Marketing managers need to understand several factors that can influence consumer desires in fulfilling needs. These factors include motivation, attitude, etc.